2016
DOI: 10.1177/0734904116680222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between European chimney test results and actual installations

Abstract: European standards regulate the certification procedure for determining chimney class temperature\ud and the distance at which to install chimneys from combustible materials. These standards\ud prescribe the heat stress test and the thermal shock test. The high number of roof fires due to\ud the presence of a chimney that have recently occurred in European countries seems to be due to\ud a weak certification procedure. In this article, experimental tests and numerical simulations have\ud been performed to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Data presented in this paper support for previous works [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] on heat transfer at chimney-roof penetration. The data ( Fig.…”
Section: Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Data presented in this paper support for previous works [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] on heat transfer at chimney-roof penetration. The data ( Fig.…”
Section: Datasupporting
confidence: 88%
“…In the experimental campaign extensively described in [1] , [2] , [3] , [4] , [5] , a chimney of 200 mm in diameter was installed in a corner test structure ( C ) and in an axi-simmetric test structure ( A ) respectively. The test structures described in [1] , [4] are both made of an interchangeable roof.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the possible operational conditions of a metal chimney, Neri and Pilotelli [11] conducted extensive measuring tests at the chimney-roof penetration, considering real operating conditions [12] and the conditions considered in the chimney certification procedure [13]. The main differences between these two conditions were compared in [14]. In [15] a 2D and a 3D numerical models for the estimation of the steady temperature at the chimney-roof penetration were defined.…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, the fact that the actual on-site flue gas temperatures are higher than assumed in chimney design [4,5], faulty installations, use contrary to operating instructions [6] and the smouldering combustion of mineral wool insulation [6][7][8]. Previous research by Neri et al [9][10][11] and Leppa¨nen et al [4,5,12] have also shown that the standard test set-up and conditions are often different from the actual site installations and may not always lead to a safe solution. All the above issues can increase the temperatures in the roof construction.…”
Section: Introductionmentioning
confidence: 99%